BS 6789-6.2:1989. Apparatus with one or moreparticular functions for connection to public switched telephonenetworks run by certain public telecommunications operators. Specification for series connected apparatus. Apparatushaving less than maximum allowable impairments. (31st October 1992) - British Standards Institution,
No abstract available